Serial Changes in 3-Dimensional Supraspinatus Muscle Volume After Rotator Cuff Repair - Chung, Seok Won; Oh, Kyung-Soo; Moon, Sung Gyu; Kim, Na Ra; Lee, Ji Whan; Shim, Eungjune; Park, Sehyung; Kim, Youngjun (SAGE PUBLICATIONS INC, 2017)
Background: There is considerable debate on the recovery of rotator cuff muscle atrophy after rotator cuff repair. Purpose: To evaluate the serial changes in supraspinatus muscle volume after rotator cuff repair by using semiautomatic segmentation software and to determine the relationship with functional outcomes. Study Design: Case series; Level of evidence, 4. Methods: Seventy-four patients (mean age, 62.8 +/- 8.8 years) who underwent arthroscopic rotator cuff repair and obtained 3 consecutive (preoperatively, immediately postoperatively, and later postoperatively [> 1 year postoperatively]) magnetic resonance imaging (MRI) scans having complete Y-views were included. We generated a 3-dimensional (3D) reconstructed model of the supraspinatus muscle by using in-house semiautomatic segmentation software (ITK-SNAP) and calculated both the 2-dimensional (2D) cross-sectional area and 3D volume of the muscle in 3 different views (Y-view, 1 cm medial to the Y-view [Y+1 view], and 2 cm medial to the Y-view [Y+2 view]) at the 3 time points. The area and volume changes at each time point were evaluated according to repair integrity. Later postoperative volumes were compared with immediately postoperative volumes, and their relationship with various clinical factors and the effect of higher volume increases on range of motion, muscle power, and visual analog scale pain and American Shoulder and Elbow Surgeons scores were evaluated. Results: The interrater reliabilities were excellent for all measurements. Areas and volumes increased immediately postoperatively as compared with preoperatively; however, only volumes on the Y+1 view and Y+2 view significantly increased later postoperatively as compared with immediately postoperatively (P < .05). There were 9 patients with healing failure, and area and volume changes were significantly less later postoperatively compared with immediately postoperatively at all measurement points in these patients (P <. 05). After omitting the patients with healing failure, volume increases later postoperatively became more prominent (P < .05) in the order of the Y+2 view, Y+1 view, and Y-view. Volume increases were higher in patients who healed successfully with larger tears (P = .040). Higher volume increases were associated only with an increase in abduction power (P = .029) and not with other outcomes. Conclusion: The supraspinatus muscle volume increased immediately postoperatively and continuously for at least 1 year after surgery. The increase was evident in patients who had larger tears and healed successfully and when measured toward the more medial portion of the supraspinatus muscle. The volume increases were associated with an increase in shoulder abduction power.
Keywords: ARTHROSCOPIC REPAIR; FATTY INFILTRATION; SURGICAL REPAIR; ATROPHY; TENDON; DEGENERATION; TEARS; INTEGRITY; SEGMENTATION; STRENGTH